2016
DOI: 10.1177/0021998316681832
|View full text |Cite
|
Sign up to set email alerts
|

Healing efficiency of polystyrene electrospun nanofibers with Grubbs’ catalyst in thermosetting composite

Abstract: The study presents a novel method for the protection of Grubbs’ catalyst, by incorporation in polystyrene fibres via electrospinning technique. Epoxy-glass fibre composite with embedded self-healing agents (polystyrene fibres with Grubbs’ and microcapsules with dicyclopentadiene) was processed. Fibres retained pale purple colour during processing, revealing that fibres provided good protection of the catalyst from the amine hardener. The influence of self-healing agents’ content and thermal treatment on self-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…In this sub‐section, investigations conducted [ 22,36‐49 ] mainly targeted to SH of PCMs. In, [ 22 ] Kotrotsos and Kostopoulos incorporated two Nylon‐66 electrospun layers (pristine or modified with multi‐walled carbon nanotubes [MWCNTs]) as SHAs into quasi isotropic CFRPs, locally, at critical areas in which damage is expected to be occurred after low velocity impact testing.…”
Section: Electrospun Self‐healing Agents Intended To Self‐healing Of mentioning
confidence: 99%
See 3 more Smart Citations
“…In this sub‐section, investigations conducted [ 22,36‐49 ] mainly targeted to SH of PCMs. In, [ 22 ] Kotrotsos and Kostopoulos incorporated two Nylon‐66 electrospun layers (pristine or modified with multi‐walled carbon nanotubes [MWCNTs]) as SHAs into quasi isotropic CFRPs, locally, at critical areas in which damage is expected to be occurred after low velocity impact testing.…”
Section: Electrospun Self‐healing Agents Intended To Self‐healing Of mentioning
confidence: 99%
“…Experimental results revealed that by fibers incorporation, not only improved the initial mechanical properties, but also resulted in SH materials able to recover its initial impact properties up to four times. Radovic et al, [ 41 ] presented a novel method for Grubbs' catalyst protection by incorporation of it into electrospun PS fibers. These core‐shell fibers and microcapsules containing DCPD were embedded into a glass fiber reinforced plastic (GFRP) material to provide SH.…”
Section: Electrospun Self‐healing Agents Intended To Self‐healing Of mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] The extensive crosslinking network within PDCPD contributes to high heat and impact resistance, [6][7][8] making it an attractive material for further applications including composite materials, [9][10][11] aerogels, 12,13 and self-healing polymers. [14][15][16] However, PDCPD has a low surface energy when freshly prepared, making it difficult to process or modify, and its lack of chemical functionality -beyond just residual double bonds -limits its broader applications. 17 To address the low surface energy of PDCPD, and to bestow additional function to the polymer, we installed a C-linked ester group on the dicyclopentadiene monomer.…”
Section: Introductionmentioning
confidence: 99%